Analyzing the Correlation Between Inflation Rates and Economic Growth: A Case Study in Central Kalimantan Province - Muhammad Farras Nasrida; Sabirin Sabirin; Dedi Takari; Ringgo Saprianto; Yuliana Hellen E; Dina Lorensa; Sutri Trisna Dahlia; Enzelly Robby Rangkap; Naya Deswity Pasha E; Widya Ayu Safitri (Jurnal Ekonomi dan Pembangunan Indonesia, 2023)
Inflation in Central Kalimantan is a rise in the cost of products and services that occurs generally in all countries or regions. Inflation can have a major impact on Central Kalimantan's economic expansion. It seeks to look into how inflation and economic growth are related in Central Kalimantan from 2011-2021. Simple regression is used in this study. The inflation variable (X) has a positive regression coefficient (B) of 0.320 in the t-test, or partial significance test, with a significance threshold of 0.076 or greater than the 0.05 significance level. Inflasi variable greater than 0.556, or 55.5%, has a detrimental effect on economic expansion, and 100 percent less than 55.5% equals 44.5%. According to these findings, rising inflation will have an adverse effect on Central Kalimantan's economic growth from 2011 to 2021. In other words, economic growth will slow down when inflation increases.